Cytological, molecular, and clinical features of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features versus invasive forms of follicular variant of papillary thyroid carcinoma. Issue 5 (13th February 2017) - Zhao, Liena; Dias‐Santagata, Dora; Sadow, Peter M.; Faquin, William C.
Abstract : BACKGROUND: The noninvasive follicular variant of papillary thyroid carcinoma (PTC) has an indolent clinical behavior in comparison with other PTCs, including the invasive follicular variant of papillary thyroid carcinoma (IFVPTC). Recently, the term noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) was introduced to emphasize the low biological potential of these tumors. This study compares clinical, cytological, and molecular features of NIFTP and IFVPTC. METHODS: The study consisted of 97 thyroid fine‐needle aspiration biopsy (FNAB) cases with corresponding surgical pathology from the pathology archives of the Massachusetts General Hospital. The collected patient data included the following: age, sex, type of surgery, tumor size, and prior cytological diagnosis with The Bethesda System for Reporting Thyroid Cytopathology. A molecular analysis using anchored multiplex polymerase chain reaction was performed for all cases. Each case was reviewed and subclassified histologically as NIFTP or IFVPTC. Cytology slides were scored semiquantitatively for nuclear atypia. The statistical analysis was performed with the nonparametric Mann‐Whitney test. RESULTS: The 97‐case cohort consisted of 50 NIFTP cases and 47 IFVPTC cases, including 18 encapsulated IFVPTC cases and 29 nonencapsulated IFVPTC cases. Differences in the type of surgery ( P = .0399), molecular features ( P = .0141), cytological classification ( P = .0266), and nuclear scores ( P = .0141) between NIFTP and IFVPTC were observed. There was overlap in the cytological classification of NIFTP and IFVPTC; however, NIFTP was more often classified as atypia of undetermined significance/follicular lesion of undetermined significance or follicular neoplasm/suspicious for follicular neoplasm in comparison with both subsets of IFVPTC. NIFTP was primarily associated with mutations in RAS, whereas an equal number of IFVPTC cases were associated with BRAFV600E or with RAS mutations. CONCLUSIONS: Despite differences in the cytological classification and molecular profiles between NIFTP and IFVPTC, the degree of overlap makes it unlikely that most cases of NIFTP and IFVPTC can be accurately distinguished with FNAB. Cancer Cytopathol 2017;125:323–331. © 2017 American Cancer Society. Abstract : Despite significant differences in the cytological classification and molecular profiles of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features and the invasive follicular variant of papillary thyroid carcinoma, the degree of overlap makes it unlikely that most cases can be accurately distinguished by fine‐needle aspiration biopsy.